DESIGN OF DYNAMIC STRUCTURAL MODELS OF INFORMATION MANAGEMENT SYSTEM OF MOVING OBJECTS - Korobchynskyi, Maksym; Mashkov, Oleg (Informatyka, Automatyka, Pomiary w Gospodarce i Ochronie Środowiska, 2013)
In the following work the authors attempt to find the best way to design a dynamic structural model of information management system of moving objects. This structural model allows organizing various management systems of moving objects, considering the spatial and time dependencies between the key components or parameters of the said management system. An example of such system may be a group of UAVs.